STATE REGULATION INSTITUTIONAL FEATURES OF FOREIGN TRADE ACTIVITY IN RUSSIA - Ekaterina Nikolayevna Strakhova (Advanced Engineering Research)
The correlation issues of the state regulation organizational and institutional component of the foreign trade activity in Russia are considered. The factual data on the federal executive bodies operation during the period from 1992 to 2011 is gathered and analyzed. With consideration of these indices, the basic elements of the mechanism of forming path dependence in the foreign trade activity are selected. The key element of this mechanism is the cyclicality of the organizational and institutional development. In terms of the organizational component, the cycles under discussion are time ranges — from maximum to minimum amount of the performed organizational changes. In terms of the institutional component, these cycles are time spans when the priority of the certain trends of the state regulation and measures of state support for the foreign trade activity is observed. The perceived cyclicality is determined by the great accumulation of the factors of the organizational and institutional imbalances in the institutional system of the foreign trade activity. These imbalances are regarded as temporary discordance in the sphere of the legal support for education, abolition and functioning of the executive authorities responsible for the regulation and support for the foreign trade activity.